Motherland in danger : Soviet propaganda during World War II - Berkhoff, Karel C. 1965- (Harvard Univ. Press, 2012)
Stalinist propaganda as a system for control -- Selfless obedience and heroism at the front -- A single forced labor camp -- Material privations -- Monstrous atrocities -- A bestial plan for physical extermination -- Hatred with all the might of the soul -- The motherland and its peoples -- Immortal avengers and enemy accomplices -- Allies who must join the action